Solitary fibrous tumor of the kidney: a report of two cases - Rui Pedro Caetano M. Oliveira; Edgar Miguel C. L. T Silva; Carol dos Anjos Marinho; José Ignacio Lopez; Lígia Romana O. A. P. Castro
ABSTRACT Solitary fibrous tumor (SFT) is a rare mesenchymal neoplasm, composed of monotonous spindle cells, intermingled with collagen fibers. Kidney location is sporadic, with few reports in literature. We present two cases of 40- and 48-year-old males, one with incidental detection of a peripheral mass; another with hilar lesion perceived following investigation of hematuria. Both revealed a spindle-cell proliferation, without mitosis and necrosis. Immunohistochemical studies: positivity for CD34, CD99 and B-cell lymphoma 2 (Bcl-2). No sign of disease were evident nine and five months after surgery, respectively. SFT is mostly benign, but can show malignant behavior. Morphologic and immunohistochemical characteristics are essential for diagnosis.